A rare case of inflammatory myopathy - P., Praveen M.; Shanmugam, Lokesh; Prashanth, Akshay (International Journal of Advances in Medicine, 2020)
Idiopathic inflammatory myopathies (IIMs) happened to be the group of heterogeneous, systemic rheumatic diseases including adult polymyositis (PM), adult dermatomyositis (DM), myositis accompanied with another connective disease or cancer. A 52 years old male patient with known history of type 2 diabetes mellitus presented with complaints of muscle pain and swelling over left arm. These cases was successfully treated by using Corticosteroids. This cases study described the clinical presentation and features of inflammatory myositis. Although this is a rare case, its clinical features and treatment procedure helps in management of similar cases.